INDOOR RADON MONITORING IN SELECTED BUILDINGS IN VYDRNÍK (VIKARTOVCE FAULT, SLOVAKIA). Issue 9 (22nd August 2022) - Smetanová, Iveta; Mojzeš, Andrej; Csicsay, Kristian; Marko, František
Abstract: To test the relation of indoor radon concentration to fault zone, a survey was conducted in selected buildings in Vydrník, situated close to the neotectonically active Vikartovce fault trace. Monitoring was performed using RamaRn track detectors during a period of 1 year. Annual average of indoor radon ranged from 60 to 940 Bq/m 3, with an average of 160 Bq/m 3 . Seasonal variation of indoor radon concentration was confirmed, with minimum in summer (June–August). The results confirmed that radon concentration in rooms above the cellar was lower than in rooms with the direct contact with subsoil. High indoor radon up to 940 Bq/m 3 was detected only in one of monitored houses situated close to the generally E–W trending Vikartovce fault and can be attributed to this fault zone used as pathway for radon migration. Influence of nearby situated NW–SE trending crosscutting fault on radon concentration is probable too.